Factors Related to Health Management and Infectious Diseases in Correctional Institution Inmates - Marsela Riska Raswandaru; Rosiana Eva Rayanti; Hermina Gaudia Kembarimop Mangguwop (Universitas Malahayati Lampung, 2026)
ABSTRACT Prisoners often suffer from HIV, TB, and scabies. In 2019, 51% of prisoners were infected with HIV, 7,972 prisoners had TB in 2020, and 76.9% had scabies in 2022. High population density, low socioeconomic status, poor sanitation, promiscuous sexual behavior, and misdiagnosis are the causes of infectious diseases among inmates. This necessitates a comprehensive health management program to address infectious disease issues. To determine the factors related to health management and infectious diseases, namely HIV, TB, and scabies, among inmates in correctional facilities. This study used a quantitative method with a cross-sectional design. Data analysis was performed using frequency and Spearman's tests for correlation. The study was conducted in the Correctional Facility from December 2025 to February 2026 with a population of all inmates. The study sample consisted of 245 respondents. The majority of respondents were male, numbering 221 (90.2%), with the highest level of education being 118 (48.2%), length of detention being 118 (48.2%), and normal blood pressure being 237 (96.0%). There was a significant relationship between health management and length of detention (p=0.015), HIV (p=0.004), TB (p=0.003), and scabies (p=0.001). In addition, there was a relationship between HIV and highest level of education (p=0.000) and blood pressure (p=0.030). There was a relationship between scabies and TD (p=0.039). Health management in correctional facilities needs to be strengthened in a comprehensive and coordinated manner, with nurses playing a role in implementing an integrated promotive, preventive, curative, and rehabilitative approach, as well as cross-sector collaboration, in order to reduce the risk of infectious diseases and improve the quality of life of inmates. Keywords: Correctional Facilities, Disease management, HIV, Scabies, TB Abstrak Warga binaan pemasyarakatan (WBP) sering mengalami HIV, TB, Skabies. Prevelensi tahun 2019 sebanyak 51% orang terkena HIV, sebanyak 7.972 WBP mengalami TB di tahun 2020, sedangkan Skabies menjadi penyakit 76,9% pada tahun2022. Kondisi kepadatan penghuni yang tinggi, keadaan sosial ekonomi yang rendah, sanitasi yang buruk, perilakuseksual yang bebas dan kesalahan diagnosis menjadi penyebab WBP terkena penyakit menular. Hal tersebutmenyebabkan adanya kebutuhan program manajemen kesehatan yang menyeluruh untuk menangani permasalahan penyakit menular. Untuk mengetahui faktor-faktor yang berhubungan antara manajemen kesehatan dan penyakit menular HIV, TB dan Scabies pada WBP di Area Pemasyarakatan. Penelitian ini menggunakan metode kuantitatif dengan desain cross sectional. Analisis data dilakukan menggunakan uji frequensi dan spearman untuk hubungan. Penelitian dilakukan di Area Pemasyarakatan pada Desember 2025-Februai 2026 dengan populasi seluruh WBP. Sampel penelitian ini berjumlah 245 responden. Mayoritas responden berjenis kelamin laki-laki sebanyak 221 (90.2%), pendidikan terakhir sebanyak 118 (48.2%), lama tahanan sebanyak 118 (48.2%), tekannan darah normal sebanyak 237 (96.0%). Terdapat hubungan signifikan antara manajemen kesehatan dengan lama tahanan (p=0.015), HIV (p=0.004), TB (p=0.003), Scabies (p=0.001). Selain itu, terdapat hubungan antara HIV dan pendidikan terakhir (p=0.000) dan TD (p=0.030). Hubungan antara Scabies dan TD (p=0.039). Manajemen kesehatan di area pemasyarakatan perlu diperkuat secara komprehensif dan terkoordinasi, dengan peran perawat yang menjalankan pendekatan promotif, preventif, kuratif dan rehabilitatif secara terpadu, serta kolaborasi lintas sektor, guna menurunkan risiko penyakit menular dan meningkatkan kualitas hidup WBP. Kata Kunci: Area Pemasyarakatan, HIV, Manajemen Penyakit, Scabies, TB